Crimes against nature environmental criminology and ecological justice - White, R. D. (Robert Douglas) 1956-; Gale Group (Cullompton, U.K. Portland, Or. Willan, 2008)
Provides an account and analysis of the key concerns of green criminology. Provides numerous examples of crimes against the environment - ranging from toxic waste, logging, wildlife smuggling, bio-piracy, the use and transport of ozone depleting substances through to illegal logging and fishing, water pollution and animal abuse.
pt. 1. Green theoretical perspectives -- pt. 2. Environmental crime -- pt. 3. Responding to environmental harm.
Electronic reproduction.
Keywords: Offenses against the environment; Offenses against the environment -- Prevention; Animal welfare; Electronic books